Poslušanje glasbe kot strategija spoprijemanja s stresom v času pandemije covida-19 - Galič, Nastja (Glasbenopedagoški zbornik (Ljubljana), 2022)
: In this paper, we explore music listening as an important coping strategy during the COVID-19 pandemic. During the COVID-19 pandemic, the participants used more constructive than non-constructive strategies for coping with stress. They also used listening to music for coping. Participants listened to more music during the pandemic than before the pandemic. Most participants reported that music was important to them. These participants used listening to music as a coping strategy more often than the other participants. We found that there are differences between the participants in the use of listening to music as a coping strategy according to family environment and age, and that listening to music is associated with different coping strategies.
Keywords: coping style; covid-19; glasba; music; strategije spoprijemanja; stres; stress